Heat Stress Decreases Intestinal Physiological Function and Facilitates the Proliferation of Harmful Intestinal Microbiota in Sturgeons - Yang, Shiyong; Zhang, Chaoyang; Xu, Wenqiang; Li, Datian; Feng, Yang; Wu, Jiayun; Luo, Wei; Du, Xiaogang; Du, Zongjun; Huang, Xiaoli (Frontiers in Microbiology, 2022)
Heat is a common source of stress in aquatic environments and can alter the physiological and metabolic functions of aquatic animals, especially their intestinal function. Here, the effects of heat stress on the structure and function of the intestine and the characteristics of the intestinal microbiota were studied in sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂ hybrid F1). Sturgeons were exposed to sub-extreme (24°C) and extreme (28°C) high water temperatures for 12 days. The heat stress caused systemic damage to the intestine of sturgeon, which displayed severe enteritis in the valve intestine. The microbial diversity analysis showed that heat stress led to the disorder in intestinal microbiota, manifesting as an explosive increase in the abundance of thermophilic intestinal pathogens such as Plesiomonas, Cetobacterium and Aeromonas and causing physiological dysfunction in the sturgeon. The disorder was followed by significant inhibition of intestinal digestion with reduced chymotrypsin, α-amylase and lipase activities in the valve intestine and of antioxidant function with reduced POD and CAT activity. Simultaneously, heat stress reduced the thermal tolerance of sturgeon by reducing Grp75 expression and damaged the valve intestine’s repair ability with increased Tgf-β expression. The results confirmed that heat stress damaged the sturgeon’s intestines obviously, and disturbed the intestinal microbiota, resulting in serious physiological dysfunction. The present study investigated the mechanism of the effect of heat stress on a sturgeon’s intestine and will help develop strategies to improve the resistance to thermal stress for wild and cultured sturgeons.